Tafsir Scholar's View on Black Magic - Suhemi, Emi (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2023)
This study aims to discuss black magic (sihir) from the perspective of Tafsir scholars. The method used in this article is literature review with a hermeneutic approach, also known as tafsir maudhu'i. With this method, the author conducts various steps, including collecting literature and verses with the theme of magic in the Quran, collecting hadiths with the theme of magic, and also using dictionaries as tools to find the etymological use for black magic. The results of this study show that the tafsir scholars have agreed on the sinful practice of black magic, so they suggest staying away from themselves, their families, and loved ones rather than this great slander and harm that has swallowed up many people. Even if we are rich and happy because of black magic, it really is not comparable to the poverty and suffering that will be accepted in the hereafter.